Pengenalan Jajanan Tradisional Kepada Siswa SD di Malang melalui Boardgame - Shella Dwi Pramaysari; Eva Handriyantini; Mahendra Wibawa (LPPM STIKI Malang, 2022)
The subject of souvenirs which discusses traditional local snacks is already provided in the thematic book. This book is published by the government for elementary grade and is also used in SDN Pisangcandi 2 Malang. The subject itself is simple, but yet considered not optimally absorbed by students due to the absence of learning support media that can be used to facilitate the teaching and learning process. The solution offered for this problem is to create a board game as an interactive learning media. This media will be able to improve learning outcomes related to the topic of traditional snacks. Boardgame as an interactive media also can create children's interactions with each other and minimizing addiction to other electronic devices such as smartphones or tablets. The method used in this research is a design method that begins with the concept phase, the design phase, and prototyping before reaching the final result. This Djatra board game is made using a storyline that can make the player animate the character's role. This research outcome is a full set of boardgame packaged with attractive visuals, adapted to the characteristics of students to make them interesting and making it easier to understand the subject comprehensively